The alkali-carbonate reaction and its reaction products an experience with argentinean dolomite rocks - Milanesi, Carlos Alberto (1996)
Three dolomitic rocks from Argentina were studied under different test conditions (ASTM C 586, ASTM C 227, CSA A23.2-14A, powdered rock samples immersed in strong alkali Solutions). X-ray diffraction (XRD), optical microscopy (OM) and scanning electrón microscopy (SEM) analyses of the various reaction producís detected under these conditions are presented. Results are compared with the alkali expansivity of the dolomitic rocks and are also used to discuss the scope and applicability of the different reaction mechanisms proposed in the literature. It has been concluded ffom this research that the mechanism originally proposed by Hadley is adequate to explain the reaction mechanisms that opérate in concrete structures under natural Service conditions.